Ferromagnetically coupled dinuclear MII complexes based on a boratriazine ligand framework. Issue 42 (3rd October 2018) - Savard, Jamie M.; Brunet, Gabriel; Srinivasan, Anandi; Murugesu, Muralee; Brusso, Jaclyn L.
Abstract : The structural and magnetic properties of dinuclear Fe II and Co II complexes, synthesized through the targeted use of mer -coordinating boratriazine and azido bridging ligands are presented, which exhibit large spin ground states due to ferromagnetic interactions. Abstract : A boratriazine ligand, which incorporates attractive features from both bodipy and terpy, has been used to synthesize [Fe2 II ( μ 1, 1 -N3 )2 (Py2 F2 BTA)2 (N3 )2 ] (1 ) and [Co2 II ( μ 1, 1 -N3 )2 (Py2 F2 BTA)2 (N3 )2 ] (2 ). Both1 and2 feature a double end-on azido bridging motif, which promotes ferromagnetic interactions between the metal centres. Indeed, 1 represents the first report of a dinuclear Fe II complex with this bridging mode exhibiting J = 5.7(9) cm −1 and D = −6.0(4) cm −1, while the isostructural Co analogue shows J = 7.1(9) cm −1 and D = 17.3(9) cm −1 .